A new species of Hohenbergia (Bromeliaceae) from Bahia, Brazil - Maciel, Jefferson Rodrigues; Louzada, Rafael Batista (Phytotaxa, 2014)
In this paper a new species of Hohenbergia from Bahia, Brazil, H. lativaginata, is described. Compared with 4 other related species and illustrated.